Clinical Characteristics and Treatment Patterns Among Patients Diagnosed With Cluster Headache in U.S. Healthcare Claims Data. Issue 9 (5th June 2017) - Choong, Casey K.; Ford, Janet H.; Nyhuis, Allen W.; Joshi, Shivang G.; Robinson, Rebecca L.; Aurora, Sheena K.; Martinez, James M.
Abstract : Objective: To characterize demographics, clinical characteristics, and treatment patterns of patients with cluster headache (CH). Background: CH is an uncommon trigeminal autonomic cephalalgia with limited evidence‐based treatment options. Patients suffer from extremely painful unilateral headache attacks and autonomic symptoms with episodic and chronic cycles. Design/Methods: This retrospective analysis used insurance claims from Truven Health Analytics MarketScan ® research databases from 2009 to 2014. Two cohorts were compared: CH patients (with ≥2 CH claims) were propensity score matched with 4 non‐headache controls, all with continuous enrollment for 12 months before and after the date of first CH claim or matched period among controls. Results: CH patients (N = 7589) were mainly male (57.4%) and 35‐64 years old (73.2%), with significantly more claims for comorbid conditions vs controls (N = 30, 341), including depressive disorders (19.8% vs 10.0%), sleep disturbances (19.7% vs 9.1%), anxiety disorders (19.2% vs 8.7%), and tobacco use disorders (12.8% vs 5.3%), with 2.5 times greater odds of suicidal ideation (all P  < .0001). Odds of drug dependence were 3‐fold greater among CH patients (OR = 2.8 [95% CI 2.3‐3.4, P  < .0001]). CH patients reported significantly greater use of prescription medications compared with controls; 25% of CH patients had >12 unique prescription drug claims. Most commonly prescribed drug classes for CH patients included: opiate agonists (41%), corticosteroids (34%), 5HT‐1 agonists (32%), antidepressants (31%), NSAIDs (29%), anticonvulsants (28%), calcium antagonists (27%), and benzodiazepines (22%). Only 30.4% of CH patients received recognized CH treatments without opioids during the 12‐month post‐index period. These patients were less likely to visit emergency departments or need hospitalizations (26.8%) as compared to CH patients with no pharmacy claims for recognized CH treatments or opioids (33.6%; P  < .0001). Conclusions: The burden of CH is associated with significant co‐morbidity, including substance use disorders and suicidal ideation, and treatment patterns indicating low use of recognized CH treatments.